SUPPLY CHAIN ANALYSIS OF RAW MATERIAL AVAILABILITY IN FAST FOOD INDUSTRY OF MCDONALD’S MALANG - Felicia Anggawinata (Journal of International Conference Proceedings (JICP), 2018)
This research is important to understand how supply chain management, especially related to the supply of raw materials in the food and beverage industry, specifically in international franchising companies. This paper contains a study of supply chain management at the international franchise company "Mcdonald's"for the selection of suppliers directly related to the supply of raw materials and basically the branches located at Jalan Brigadier General Slamet Riadi Malang, East Java. The selection of suppliers of this research is carried out using data collection methods from interview systems and document collection as research material. This is to enable systematic and easy results for processing this research. I choose supplier selection theory because the supply chain of raw materials from suppliers strongly influences the good name of a company. Therefore, Mcdonald needs a supplier which must be consistent about the quality and quantity that are providedso that Mcdonald is able to satisfy their customers. Keywords : Supply chain , Supplier , raw materials , international frainchashing , food and beverages,